Homelessness Service Provision in a Southern European Country: An Evolving Sector Framed by the Portuguese National Homelessness Strategy - Baptista, Isabel; Coelho, Miguel (Κοινωνική Πολιτική, 2021)
This article aims to provide a critical overview of homelessness service provision in Portugal – framed by EU-level developments with a particular focus on Southern European countries – within the national policy dynamics that in recent years have evolved towards the adoption of a national strategic approach to resolving homelessness. The article maps the organisational and operational changes which the provision of homelessness services has undergone in recent years, while also highlighting the stabilities that continue to shape the sector. The analysis provided will mainly draw on national evidence on the role and operation of the homelessness sector in Portugal and on available reviews on the adoption and implementation of the two national homelessness strategies. The topic has received little research and policy attention so far, which may partly be explained by the fragmented nature of the sector itself and by the only recent emergence of homelessness as an item on the Portuguese political agenda.